IDENTIFIKASI Verocytotoxigenic Escherichia coli (VTEC) PADA ISOLAT ASAL SUSU DAN LINGKUNGAN PETERNAKAN DENGAN METODE POLYMERASE CHAIN REACTION (PCR) - , Arbyan Umbu Reku Landuwulang, Dr. drh. Yatri Drastini, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Verocytotoxigenic Escherichia coli is one of the group of pathogenic E. coli in human. These bacteria are distinguished to others by produce verotoxin. O157:H7 serotype can cause haemorrhagic colitis (HC), hemolytic uremic syndrome (HUS) and thrombotic thrombocytopenic purpura (TTP) in humans while rarely cause illness in animals. Ruminants, especially cattle are the primary reservoir of VTEC. This bacterium infects humans through contaminated food or water. The purpose of this research is to detect vt1 and vt2 gene to find out the presence of VTEC in the milk produced on the farm and in the farm environment including water, feces, feed, soil and hand swab of the milker. An amount of 76 isolates of E. coli consisted of 27 isolates of milk, 11 isolates of water, 14 isolates of fecal, 6 isolates of feed, 1 isolate the of soil around the cage, and 17 isolates of the hand swab of milkers were examined to detect the presence of VTEC. Identification of VTEC was conducted by inoculation samples on sorbitol- MacConkey agar (SMAC) and detection of vt1 and vt2 gene by Polymerase Chain Reaction (PCR). Colorless colonies on SMAC were suspected as E. coli serotype O157: H7. The vt1 gene was detected by a pair of primers based on the design of pollard et al. (1990)